1995
DOI: 10.1111/j.1365-2923.1995.tb02836.x
|View full text |Cite
|
Sign up to set email alerts
|

How do clinicians learn to request permission for autopsies?

Abstract: A postal survey of 434 clinicians at four local hospitals was undertaken in order to identify the methods by which clinicians learn how to request permission for hospital autopsies and to assess the preferred techniques and timing of relevant communication skills training. The majority of 128 responding clinicians had learnt through personal experience with some assistance from senior colleagues and peers. Few clinicians appeared to have learnt through formal training. The preferred methods for the provision o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…24 Many qualified doctors would benefit from training since most of them have never received educational sessions on bad news whilst at the same time they act as role models for their younger colleagues and thereby influence actual clinical practice.6,25 Last but not least it has to be taken into account that organizational and structural factors can either assist or undermine doctors in their efforts to put into practice ethically sound and skilled communication when disclosing bad news. Given that organizational factors and work pressures make it hard to maintain the highest standards which we are teaching undergraduates to aim for, there needs to be both a recognition of these constraints, efforts to change those which could be changed and opportunities for postgraduate education to build upon the undergraduate teaching and to address the situations of bad news that doctors are now dealing with.…”
Section: Methodsmentioning
confidence: 99%
“…24 Many qualified doctors would benefit from training since most of them have never received educational sessions on bad news whilst at the same time they act as role models for their younger colleagues and thereby influence actual clinical practice.6,25 Last but not least it has to be taken into account that organizational and structural factors can either assist or undermine doctors in their efforts to put into practice ethically sound and skilled communication when disclosing bad news. Given that organizational factors and work pressures make it hard to maintain the highest standards which we are teaching undergraduates to aim for, there needs to be both a recognition of these constraints, efforts to change those which could be changed and opportunities for postgraduate education to build upon the undergraduate teaching and to address the situations of bad news that doctors are now dealing with.…”
Section: Methodsmentioning
confidence: 99%
“…Without exposure to autopsy, clinicians are unlikely to become advocates of autopsy6 10 or have the skills necessary for sensitively requesting postmortem examinations 18. The public generally accepts the need for autopsy, but families are unlikely to grant consent if they feel stressed or do not fully understand why a postmortem is required 19.…”
Section: Advocating Autopsiesmentioning
confidence: 99%
“…Attitude surveys have found that trainees find the task unpleasant, are concerned with upsetting families, and believe they have been inadequately prepared to conduct inquiries and answer family questions [19,20]. Sherwood and colleagues in a survey of practicing physicians found that few had any formal instruction in how to inquire about an autopsy [21].…”
Section: Discussionmentioning
confidence: 99%